Isolation and screening of newly isolated bacteria producing nanocellulose from rotten banana skin and sugarcane bagasse - Yusoff Sayuti, Nurul Hidayah; Jimat, Dzun Noraini; Azmi, Azlin Suhaida; Ahmad Raus, Raha; Amid, Azura; Jamal, Parveen (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Cellulose is naturally available polysaccharides that are abundantly found on the earth. Plant-based cellulose and bacterial cellulose are the two types of cellulose that have been studied until this present. Bacterial cellulose is pure compared to the plant-based cellulose which consists of other components such as hemicelluloses and lignin and need to be treated prior to make it pure. Thus, bacterial cellulose is selected as the alternative cellulose instead of plant-based cellulose due highly polluted chemical products emitted from the cellulose treatments in order to decrease the global environmental issue, finding a new strain that can produce high yield of cellulose and low cost of cellulose production. This project was carried out to isolate and characterize newly bacteria producing cellulose from banana skin (BS) and sugarcane bagasse (SB) through biochemical tests. BS 1 and SB 2 isolates were selected for further study as both isolates produced high cellulose. Four biochemical tests were conducted on the selected isolates with respect to morphology, gram staining, catalase and oxidase. The results showed the isolates were gram negative and rod-shaped. The catalase tests for both isolates were negative but showed positive respond for oxidase tests.